Manufaktur Bodi Kendaraan Shell ECO Marathon (SEM) Tipe Urban Bahan Komposit Serat Karbon - Sutarto, Sutarto; Badri, Muftil (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
In the development of manufacturing industry the use of composite materials began to be widely used. One of them is composite by using fiber glass or fiber carbon, because of its characteristic that can be designed close to certain needs. In addition the specific strength and stiffness are far exceeding the engineering material in general. This research uses carbon fiber composite material as vehicle body material Shell Eco Marathon (SEM), Which a fraction volume of 70% resin polyester and 30% of carbon fiber. The composite is made using Hand Lay Up method that produces vehicle body SEM of consist of main frame and styrofoam. The result of manufacturing the SEM vehicle body is obtained, so that it can be used as an Urban SEM vehicle body.Keywords: Composite, Carbon Fiber, Hand Lay Up, Shell Eco Marathon (SEM)